2020
DOI: 10.1002/brb3.1641
|View full text |Cite
|
Sign up to set email alerts
|

Classification of comorbidity in obsessive–compulsive disorder: A latent class analysis

Abstract: Objective Patients with OCD differ markedly from one another in both number and kind of comorbid disorders. In this study, we set out to identify and characterize homogeneous subgroups of OCD patients based on their comorbidity profile. Methods In a cohort of 419 adult subjects with OCD, the lifetime presence of fifteen comorbid disorders was assessed. Latent class analysis was used to identify comorbidity‐based subgroups. Groups were compared with regard to core clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…related to OCD and/or comorbid disorders may require crisis intervention followed by disorder-specific interventions (e.g., acute suicidality; life-threatening eating disorder; uncontrolled substance abuse, bipolar disorder, or psychotic disorders) (Veale et al 2009;Albert et al 2019;Dell'Osso et al 2020;Mawn et al 2020;Palombini et al 2020). Attempts to classify comorbidity in OCD to reduce heterogeneity require further research and replication (e.g., van Oudheusden et al 2020). Development of algorithms for treatment of comorbidity in OCD is beyond the scope of this paper.…”
Section: Description Of Key Termsmentioning
confidence: 99%
“…related to OCD and/or comorbid disorders may require crisis intervention followed by disorder-specific interventions (e.g., acute suicidality; life-threatening eating disorder; uncontrolled substance abuse, bipolar disorder, or psychotic disorders) (Veale et al 2009;Albert et al 2019;Dell'Osso et al 2020;Mawn et al 2020;Palombini et al 2020). Attempts to classify comorbidity in OCD to reduce heterogeneity require further research and replication (e.g., van Oudheusden et al 2020). Development of algorithms for treatment of comorbidity in OCD is beyond the scope of this paper.…”
Section: Description Of Key Termsmentioning
confidence: 99%
“…Apparently, violence was the patient's obsessive behavior. Obsessions of aggression including intimate partner violence have been reported in studies on obsessive-compulsive disorder [16][17][18][19][20][21]. The patient trustworthily claimed that he regretted the violence but was unable to control himself.…”
Section: Casementioning
confidence: 99%
“…The relevance of comorbidity in OCD has been related to various clinical correlates such as symptom severity, suicidality, and treatment response (Jakubovski et al, 2013; Torres et al, 2011, 2016). Increased comorbidity in OCD was also associated with a history of childhood trauma and with a chronic course of illness (van Oudheusden et al, 2020). Furthermore, comorbidity was a key predictor of impaired functioning and poor quality of life among patients with OCD (Huppert, Simpson, Nissenson, Liebowitz, & Foa, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, comorbidity was a key predictor of impaired functioning and poor quality of life among patients with OCD (Huppert, Simpson, Nissenson, Liebowitz, & Foa, 2009). A different line of research suggested that the classification of OCD on the basis of the comorbidity profile might contribute to a better understanding of its aetiological and pathogenic mechanisms, thus facilitating personalized treatment approaches (Nestadt et al, 2003; van Oudheusden et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation